Molybdenum composite material, molybdenum composite molded product using the same, and method for producing the molybdenum composite material
A molybdenum composite material with controlled carbide dispersibility and specific production methods addresses heat resistance and durability issues, offering cost-effective and efficient production for lithium ion battery current collectors.
Patent Information
- Application Number
- JP2024105716
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2024-06-28
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-06-28
AI Technical Summary
Existing molybdenum composite materials for negative electrode current collectors in lithium ion batteries face issues with heat resistance, durability, production cost, and production efficiency, particularly due to inadequate dispersibility of carbide particles and suboptimal sintering methods like HIP and SPS.
A molybdenum composite material composed of 2-10% carbides (Ti, Zr, Hf) with controlled Voronoi division dispersibility, produced through hot pressing, ensuring an average area of 80 μm and coefficient of variation ≤1.8, and specific particle size distributions for molybdenum and carbide powders.
The solution provides a molybdenum composite material with enhanced heat resistance, durability, and reduced production costs, suitable for applications like vapor deposition boats, with improved bending strength and hardness retention after heating.
Smart Images

Figure 0007599607000003 
Figure 0007599607000004 
Figure 0007599607000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a molybdenum composite material, a molybdenum composite material molded article using the same, and a method for producing a molybdenum composite material. [Background technology]
[0002] Conventionally, composite current collectors in which Cu is vapor-deposited on the surface of a substrate such as PET have been proposed as negative electrode current collectors for lithium-ion batteries, instead of copper foil.
[0003] A tungsten deposition boat is used for Cu deposition to produce such a composite current collector.
[0004] However, although tungsten evaporation boats have good heat resistance, they have poor durability and tend to break after just one use.
[0005] Therefore, we considered using a molybdenum alloy evaporation boat, which is based on molybdenum, which has inferior heat resistance to tungsten but excellent workability, and to which a high-melting point compound was added, but there was a problem that it was not strong enough.
[0006] Conventionally, Patent Documents 1 to 4 are known as molybdenum alloys.
[0007] In Patent Documents 1 and 2, mechanical alloying is an essential condition for adding transition metal carbide to molybdenum. However, this method is a high-energy mixing method in which carbide particles are embedded in molybdenum particles, which poses problems in terms of production cost and production efficiency.
[0008] In addition, Patent Document 1 employs a densification process using hot isostatic pressing (HIP), which also poses problems in terms of production cost and production efficiency.On the other hand, Patent Document 2 employs spark plasma sintering (SPS) as a sintering method, but SPS is a method for producing relatively small samples, which also makes it unsuitable for manufacturing deposition boats. Furthermore, Patent Document 3 discloses a material in which carbides of Ti, Zr, Hf, etc. are added to molybdenum, and a manufacturing method thereof. Patent Document 3 describes that poor dispersion of particles of carbides, etc. leads to insufficient strength, but does not specify a method for mixing powders or an index of dispersibility, and does not present any information on how to obtain good dispersibility of carbide particles in the molybdenum composite material of the present invention. Furthermore, Patent Document 3 also employs HIP as a sintering method, which also poses problems in terms of production cost and production efficiency.
[0009] Furthermore, Patent Document 4 discloses a material in which titanium carbide, hafnium carbide, zirconium carbide, or tantalum carbide is added to molybdenum. Patent Document 4 describes a method of mixing powders by preparing carbide powders such as Mo powder and TiC, and mixing them in a ball mill or the like, but does not specify an index of dispersibility.
[0010] In any case, according to Patent Documents 1 to 4, for molybdenum alloys, the dispersibility of molybdenum powder and additive particles and the sintering state seem to be problems, but there is a need for a molybdenum composite material that is excellent in the targeted heat resistance and durability, and is also excellent in terms of production cost and production efficiency. [Prior art documents] [Patent documents]
[0011] [Patent Document 1] Patent No. 3271040 [Patent Document 2] Patent Publication No. 2000-129389 [Patent Document 3] Patent No. 5546880 [Patent Document 4] Patent No. 5238259 Summary of the Invention [Problem to be solved by the invention]
[0012] However, it was found that the heat resistance, workability, strength, and other durability of the obtained material vary greatly depending on the combination of various conditions, such as the particle size of the raw powder, the conditions for crushing and grinding the raw powder, the mixing conditions, the sintering conditions, and the molding conditions. In particular, the dispersibility of the powder in the molybdenum composite material is closely related to durability, but even a slight change in the particle size distribution of the raw materials or the hardness of the powder makes it difficult to determine the optimal combination with the mixing conditions. It was also found that the environment during mixing, especially the temperature, has a significant effect on the dispersion state.
[0013] As a result of examining various molybdenum composite materials, it was discovered that by focusing on the average area of the Voronoi tessellation of a molybdenum composite material, a molybdenum composite material with good durability can be identified, and the present invention was completed.
[0014] An object of the present invention is to provide a molybdenum composite material which is excellent in heat resistance and durability and is also excellent in terms of production cost and production efficiency, a molybdenum composite material molded product using the same, and a method for producing a molybdenum composite material. [Means for solving the problem]
[0015] In order to achieve the above object, a first aspect of the present invention is a molybdenum composite material which is a sintered body of a mixed powder of molybdenum powder and a carbide powder, the mixed powder containing molybdenum as a main component and 2 to 10 mass % of at least one carbide selected from a carbide of Ti, a carbide of Zr, and a carbide of Hf, and has an average area of Voronoi division of 80 μm 2 The molybdenum composite material has a standard deviation / average value, which is the coefficient of variation of the area of the Voronoi tessellation, of 1.8 or less.
[0016] A second aspect of the present invention is the molybdenum composite material according to item 1, which has a maximum bending strength of 1000 MPa or more at room temperature after heating in a vacuum at 1800° C. for 8 hours, and exhibits ductile deformation behavior.
[0017] A third aspect of the present invention resides in the molybdenum composite material according to item 1, which has a Vickers hardness of 200 HV or more after heating in a vacuum at 1800° C. for 8 hours.
[0018] A fourth aspect of the present invention is the molybdenum composite material according to item 3, in which a Vickers hardness reduction rate (%) before and after heating in a vacuum at 1800°C for 8 hours, calculated by subtracting the hardness reduction value before heating from the hardness after heating and dividing the result by the hardness before heating, is 30% or less.
[0019] A fifth aspect of the present invention resides in the molybdenum composite material according to 1, which is obtained by crushing and pulverizing the molybdenum powder and the carbide powder, mixing them, and hot pressing the mixed powder.
[0020] In a sixth aspect of the present invention, the molybdenum powder has an average particle size D obtained by a laser diffraction / scattering method. Ave The carbide powder has an average particle size D Ave 6. The molybdenum composite material according to claim 5, wherein the average particle diameter is 1.5 to 3.0 μm and the median diameter D50 is 1.0 to 2.5 μm.
[0021] The seventh aspect of the present invention is a method for producing the mixed powder having an average particle size D Ave 6. The molybdenum composite material according to claim 5, wherein the average particle diameter is 1.5 to 3.5 μm and the median diameter D50 is 1.0 to 3.0 μm.
[0022] An eighth aspect of the present invention is a molybdenum composite material molded article obtained by molding any one of the molybdenum composite materials according to 1 to 7 into a predetermined shape.
[0023] A ninth aspect of the present invention includes a step of preparing a molybdenum powder and at least one carbide powder selected from a carbide powder of Ti, a carbide powder of Zr, and a carbide powder of Hf in a predetermined ratio, a step of crushing and grinding the molybdenum powder and the carbide powder, and mixing them to obtain a mixed powder, and a step of sintering the mixed powder to obtain a sintered body mainly composed of molybdenum and containing at least one carbide selected from a carbide of Ti, a carbide of Zr, and a carbide of Hf in a range of 2 to 10 mass %, and the sintered body has an average area of Voronoi division of 80 μm 2 and obtaining a molybdenum composite material having a standard deviation / average value, which is a coefficient of variation of the area of Voronoi division, of 1.8 or less.
[0024] A tenth aspect of the present invention is the method for producing a molybdenum composite material according to claim 9, wherein the step of obtaining the sintered body is carried out by hot pressing (HP) at a temperature of 1400°C or higher and 1800°C or lower.
[0025] In an eleventh aspect of the present invention, the molybdenum powder has an average particle size D obtained by a laser diffraction / scattering method. Ave The carbide powder has an average particle size D Ave 10. The method for producing a molybdenum composite material according to claim 9, wherein the average particle diameter is 1.5 to 3.0 μm and the median diameter D50 is 1.0 to 2.5 μm.
[0026] The twelfth aspect of the present invention is a method for producing the mixed powder having an average particle size D Ave 12. The method for producing a molybdenum composite material according to claim 11, wherein the average particle diameter is 1.5 to 3.5 μm and the median diameter D50 is 1.0 to 3.0 μm.
[0027] A thirteenth aspect of the present invention resides in the method for producing a molybdenum composite material according to 9, wherein the step of crushing, pulverizing and mixing the molybdenum powder and the carbide powder is carried out by a rod mill.
[0028] A fourteenth aspect of the present invention resides in a method for producing a molybdenum composite material molded article, comprising molding a molybdenum composite material produced by any one of the molybdenum composite materials recited in 1 to 7 or any one of the methods for producing a molybdenum composite material recited in 9 to 13 into a predetermined shape to obtain a molybdenum composite material molded article. Effect of the Invention
[0029] According to the present invention, it is possible to provide a molybdenum composite material which is excellent in heat resistance and durability and is also excellent in terms of production cost and production efficiency, a molybdenum composite material molded product using the same, and a method for producing a molybdenum composite material. [Brief description of the drawings]
[0030] [Figure 1] This is an example of an image in which carbide particles are identified as black particles through image processing in a scanning electron microscope (SEM) image of a sample in which carbide particles are densely present and uniformly dispersed. [Diagram 2] FIG. 2 is a diagram showing the Voronoi regions in black for the particles in FIG. 1. [Diagram 3] This is an example of an SEM image of a sample in which carbide particles are densely present but not uniformly dispersed, and the carbide particles have been identified as black particles through image processing. [Figure 4] FIG. 4 is a diagram showing Voronoi regions in black for the particles in FIG. 3. [Diagram 5] This is an example of an SEM image of a sample in which carbide particles are not densely present but are uniformly dispersed, and the carbide particles have been identified as black particles through image processing. [Figure 6] The Voronoi regions for the particles in Figure 5 are shown in black. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0031] The molybdenum composite material of the present invention is a sintered body mainly composed of molybdenum and containing 2 to 10 mass % of at least one carbide selected from the group consisting of Ti carbide, Zr carbide and Hf carbide.
[0032] The molybdenum composite material of the present invention is produced using, as raw materials, molybdenum powder and at least one carbide powder selected from the group consisting of Ti carbide powder, Zr carbide powder, and Hf carbide powder.
[0033] Here, as the carbide powder, at least one type of carbide powder selected from Ti carbide powder, Zr carbide powder, and Hf carbide powder can be used, with Zr carbide powder being particularly preferred. The first reason is that when Ti carbide is partially oxidized during sintering, processing, or use, it becomes titanium oxide that easily sublimes, and can become a source of impurities in the atmosphere, especially when heated in a vacuum. The second reason is that although Hf carbide has the same effect as Zr carbide, its material price is much higher than Zr carbide, leading to increased product costs.
[0034] The molybdenum powder used as the raw material has an average particle size D Ave It is preferable to use powder having a particle size of 2.5 to 4.0 μm and a median diameter D50 of 2.0 to 3.5 μm.
[0035] The raw material carbide powder has an average particle size of D Ave It is preferable to use powder having a particle size of 1.5 to 3.0 μm and a median diameter D50 of 1.0 to 2.5 μm.
[0036] To obtain the molybdenum composite material of the present invention, the molybdenum powder and the carbide powder are crushed, pulverized, and mixed to obtain a mixed powder.
[0037] Average particle size of the resulting mixed powder D Ave It is preferable that the average particle diameter is 1.5 to 3.5 μm and the median diameter D50 is 1.0 to 3.0 μm.
[0038] In the present invention, the method for carrying out the step of crushing, pulverizing, and mixing the molybdenum powder and the carbide powder is not particularly limited as long as the desired mixed powder can be obtained, but it is preferable to carry out the step by using a rod mill (RM).
[0039] To obtain the molybdenum composite material of the present invention, the above-mentioned composite material is hot pressed (HP) at a temperature of 1400°C or higher and 1800°C or lower.
[0040] Conventionally, there is a method for obtaining sintered bodies by hot isostatic pressing (HIP), but HIP is more expensive than HP and is a method that should be avoided if possible. However, in the present invention, a sintered body having a relative density of 98% or more can be obtained by the HP method.
[0041] The molybdenum composite material of the present invention also has good heat resistant strength and heat resistant hardness, i.e., it has good bending strength after heating, good hardness after heating, and the reduction in hardness due to heating is small.
[0042] The bending strength after heating is 1000 MPa or more, preferably 1100 MPa or more, and in addition, it is preferable that the deformation behavior due to bending is ductile deformation rather than brittle fracture.
[0043] The hardness after heating is, in Vickers hardness (HV), 200 or more, preferably 220 or more.
[0044] In addition, the hardness reduction rate (%) obtained by subtracting the hardness after heating from the hardness before heating and dividing the reduction value by the hardness before heating is 30% or less, and preferably 20% or less.
[0045] In this case, "after heating" refers to a vacuum heat treatment at 1800° C. for 8 hours, taking into consideration the use as a deposition boat.
[0046] The present invention has discovered that in a molybdenum composite material, the state of dispersion of carbides is closely related to the bending strength of the molybdenum composite material, and that if the dispersion state is good and the molybdenum composite material has predetermined dispersion characteristics, there will be no unevenness in bending strength or hardness.
[0047] Here, the predetermined dispersion characteristic is that the average area of the Voronoi division is 80 μm 2The standard deviation / average value, which is the coefficient of variation of the area of the Voronoi division, is 1.8 or less, but details will be given later.
[0048] The physical properties of the molybdenum composite material of the present invention were evaluated as follows. (Bending strength) From the molybdenum composite material of the present invention, a test piece having the shape of No. 3 specified in JIS Z 2248 was cut out, and bending strength was measured by the press bending method specified in JIS Z 2248. The measuring equipment used was an Imada load measuring stand "EMX-500N" combined with a three-point bending test jig "BT-500N."
[0049] (Deformation behavior) In the above bending strength test, when the test piece was pressed 20 mm with a support distance of 20 mm, if it bent without breaking it was judged to be ductile, and if it broke it was judged to be brittle.
[0050] (Hardness) After use in the bending strength test, the undeformed portion of the end was cut off to prepare a test piece for hardness measurement, and the hardness was measured by the Vickers hardness test specified in JIS Z 2244. The measuring device used was a Mitutoyo micro Vickers hardness tester "HM-200."
[0051] Thus, the molybdenum composite material of the present invention is excellent in heat resistant strength and heat resistant hardness, but it is not clear whether the dispersion state of the carbide in the molybdenum composite material is optimal.
[0052] Even if the current heat resistant strength and heat resistant hardness are within the desired range, unless the dispersion state is grasped, there is a possibility that there will be unevenness in the heat resistant strength and heat resistant hardness.
[0053] Furthermore, even if the current dispersion state is optimal, the dispersion state of the carbide in the sintered body may change depending on differences in the particle size distribution of the raw material powder, even if the crushing, grinding and mixing conditions are the same, and it is not possible to always grasp that the dispersion state is good and that there is no unevenness in the current heat-resistant strength and heat-resistant hardness.
[0054] As described above, the carbide dispersion state of the molybdenum composite material of the present invention is good when the average area of the Voronoi division is 80 μm 2 It was found that this can be understood by the standard deviation / average value, which is the coefficient of variation of the area of the Voronoi division, being 1.8 or less.
[0055] The dispersibility was determined as follows. (dispersibility) After the bending strength test, the undeformed part of the end was cut off and the cross section was polished. Then, SEM images were taken at three locations at 2 mm intervals horizontally near the center of the thickness direction using a Hitachi High-Technologies Corporation electron microscope "TM4000Plus". The image analysis software "Image-J" was used to recognize the positions of the carbide particles from the difference in contrast. Next, the image was divided by a straight line that is a collection of points equidistant from the boundary between the two nearest particles using the "Voronoi" function of "Image-J". In other words, each divided region (Voronoi region) contains one carbide particle, and the area of the Voronoi region is small in places where carbide particles are densely present, and the area of the Voronoi region is large in places where carbide particles are sparsely present. The area of each region divided by the function "Voronoi" was calculated using "Image-J", and the sum of the areas was divided by the number of divided regions to obtain the average area of the Voronoi regions. Furthermore, the standard deviation of the area of the Voronoi regions was divided by the average area to obtain the coefficient of variation of the area of the Voronoi regions.
[0056] A method for grasping the dispersibility will be described below using a specific example of an image. Figure 1 shows an example of an image of a sample in which carbide particles are densely present and uniformly dispersed, where the carbide particles are identified as black particles by image processing. Furthermore, Figure 2 shows the Voronoi regions of the particles in Figure 1 in black. Two other SEM images were taken of this sample, and the results of similar image processing were also averaged, resulting in an average Voronoi tessellation area of 30 μm 2 , the standard deviation of the area is 21 μm 2 The coefficient of variation, calculated by dividing the standard deviation by the average area, was 0.7. This sample corresponds to Example 7 described below.
[0057] In addition, Figure 3 shows an example of an SEM image of a sample in which carbide particles are densely present but not uniformly dispersed, in which the carbide particles are identified as black particles by image processing. Furthermore, Figure 4 shows the Voronoi regions of the particles in Figure 3 in black. Two other SEM images were taken of this sample, and the average area and coefficient of variation of the Voronoi division were calculated in the same way as for the sample in Figure 1, including the results of similar image processing. The average area of the Voronoi division was found to be 30 μm 2 The coefficient of variation of the area was 3.2. This sample corresponds to Comparative Example 15 described later.
[0058] In addition, Fig. 5 shows an example of an image in which carbide particles are not densely present but are uniformly dispersed, and carbide particles are identified as black particles by image processing. Furthermore, Fig. 6 shows the Voronoi regions of the particles in Fig. 5 in black. Two other SEM images were taken of this sample, and the average area and coefficient of variation of the Voronoi division were calculated in the same way as for the sample in Figure 1, including the results of similar image processing. The average area of the Voronoi division was 100 μm 2 The coefficient of variation of the area was 0.8. This sample corresponds to Comparative Example 5, which will be described later.
[0059] (Meaning of the average area of Voronoi regions) The smaller the average area of the Voronoi regions obtained by the above method, the denser the carbide particles are in the molybdenum composite material as a whole. In addition, since the average area of the Voronoi regions is essentially the same as the area of the entire SEM image divided by the number of carbide particles contained in the image, the microstructure of the same molybdenum composite material can also be defined by the number of carbide particles contained in a cross section of a certain area. However, although the average area of the Voronoi regions and the number of carbide particles contained in a cross section of a certain area can determine the overall concentration of carbide particles in the molybdenum composite material, they cannot define the local variation in density of carbide particles.
[0060] (Importance of coefficient of variation) The inventors have found that the variation in density of carbide particles, in other words, the dispersibility of carbide particles, has an important effect on the physical properties of molybdenum alloys. That is, in a material in which carbide particles are dispersed in a molybdenum matrix to enhance heat resistance, what is important is not the amount of carbide particles added, but how uniformly the carbide particles are dispersed. If carbide particles are added but there are many places where carbide particles are not present locally, the molybdenum recrystallization proceeds in those places due to heating, so that the molybdenum crystal grains become locally coarse, and high heat resistance cannot be obtained as a whole composite material. Therefore, the inventors have found that the heat resistance of molybdenum composite materials can be well explained by using the coefficient of variation of the area of the Voronoi region as an index of the variation in density of carbide particles. That is, the smaller this coefficient of variation, the more uniformly the carbide particles are dispersed. From the above considerations, the molybdenum composite material of the present invention is characterized by the fact that the average area of the Voronoi region of the carbide particles is 80 μm 2 and its coefficient of variation was specified as 1.8 or less.
[0061] The average area of the Voronoi region of the carbide grains is 80 μm 2If the coefficient of variation exceeds 1.8, the recrystallization of molybdenum cannot be sufficiently suppressed overall, and the molybdenum crystal grains become coarse, resulting in a decrease in heat resistance. Also, if the coefficient of variation exceeds 1.8, there are areas where the carbide particles are sparse, and the crystal grains become coarse locally due to the recrystallization of molybdenum, resulting in a decrease in heat resistance.
[0062] In this way, in particular, the dispersibility of the carbide particles in the molybdenum composite material can be confirmed by grasping the average area and coefficient of variation of the Voronoi region of the carbide particles, and it was confirmed that the heat resistance and bending strength after heating are good, and that it is possible to grasp relatively easily. Therefore, it is possible to grasp from the average area and coefficient of variation of the Voronoi region of the carbide particles whether the dispersion state has changed due to even a slight change in the particle size distribution of the raw materials or the hardness of the powder in combination with the mixing conditions, or whether the dispersion state has been greatly affected by the influence of the environment during mixing, particularly the temperature.
[0063] Hereinafter, a method for producing a molybdenum composite material according to one embodiment of the present invention will be described.
[0064] The molybdenum composite material of the present invention has an average particle size D Ave Molybdenum powder with an average particle size D Ave A molybdenum pot is charged with a specified ratio of titanium carbide, zirconium carbide, and hafnium carbide powders with a mean particle size of 1.5 to 3.0 μm and a median diameter D50 of 1.0 to 2.5 μm. A molybdenum rod is inserted and the pot is rotated on a rotating stand for 1 to 24 hours to crush, pulverize, and mix the powders (rod mill). The average particle size D of the mixed powder is then measured. Ave The molybdenum composite material of the present invention is obtained by reducing the average particle diameter (A) to 1.5 to 3.5 μm and the median diameter (D50) to 1.0 to 3.0 μm, and then hot pressing (HP) at a temperature of 1400° C. to 1800° C. Then, the sintered body is processed into a desired shape to produce a molybdenum composite material molded product, which is a product made of the molybdenum composite material of the present invention.
[0065] (Manufacturing method point 1: Raw materials and molybdenum powder particle size after RM) The method for producing the molybdenum composite material of the present invention is to use a molybdenum-based material having an average particle size D Ave The molybdenum powder having an average particle size D of 2.5 to 4.0 μm, preferably 2.8 to 3.7 μm, and a median diameter D50 of 2.0 to 3.5 μm, preferably 2.2 to 3.3 μm, is used as a raw material, and the average particle size D of the molybdenum powder is reduced by RM. Ave The first point is to reduce the average particle size to 1.5-3.5 μm and the median diameter D50 to 1.0-3.0 μm. If the average particle size of the raw molybdenum powder is too large, it is difficult to uniformly disperse the carbide particles in RM, and if it is too small, the raw molybdenum powder aggregates and the carbide particles are difficult to uniformly disperse, so it is necessary to set it within a specified range. In addition, if the average particle size of the molybdenum powder after RM is too large, the sintering temperature becomes high and a sintered body with the specified density cannot be obtained, and if it is too small, the density rises sharply during HP, pores are trapped, and a sintered body with the specified density cannot be obtained, so it is necessary to set it within a specified range.
[0066] (Manufacturing method point 2: particle size of raw carbide powder) In addition, the method for producing a molybdenum composite material of the present invention uses an average particle diameter D Ave The second point is to use carbide powder having a mean diameter of 1.5 to 3.0 μm, preferably 1.8 to 2.7 μm, and a median diameter D50 of 1.0 to 2.5 μm, preferably 1.3 to 2.2 μm, as the raw material. If the average particle diameter of the raw carbide powder is large, the average particle diameter of the carbide powder after RM will also remain large, and even if the carbide particles are uniformly dispersed in the molybdenum, the brittleness derived from the carbide will lead to a decrease in the strength of the entire composite material, and the recrystallization inhibition effect of molybdenum will not be sufficiently obtained due to the reduction in the number of carbide particles, and the strength of the entire composite material will also decrease due to the local coarsening of molybdenum crystal grains. In addition, if the average particle diameter of the raw carbide powder is small, the average particle diameter of the carbide powder after RM will also be too small, and the carbide particles will aggregate and not be uniformly dispersed, so it is necessary to keep it within a specified range.
[0067] (Manufacturing method point 3: Rod mill and conditions) The third point is to use the above-mentioned molybdenum powder and carbide powder as raw materials, and mix the molybdenum powder and carbide powder while crushing and pulverizing the coarse particles formed by agglomeration of the primary particles of the powder by the RM. In order to perform efficient crushing and pulverization, it is desirable to set the rotation speed to 0.55 to 0.8 times the critical rotation speed [rpm] given by 42.3 / √D when the diameter of the container is D [m]. Note that the RM may be replaced with other known methods as long as it is a method that can crush and pulverize the powder while simultaneously mixing it. That is, it may be replaced with a mixing method using a grinding medium other than a rod, for example, a ball mill, or a method using other equipment, for example, a planetary ball mill, may be used as the method for rotating the pot, or a method using energy other than the kinetic energy of the grinding medium as the grinding energy, for example, a jet mill after mixing the raw molybdenum powder and carbide powder may be used. As a basis for selecting from among the many mixing methods and determining the conditions of the mixing method, it is desirable to prepare a small sample by sintering a small amount of the mixed powder and to confirm whether appropriate dispersibility is obtained using the above-mentioned method for evaluating the dispersibility of carbide particles.
[0068] The reason for setting the RM process to 1 to 24 hours is that if the process is performed for less than 1 hour, the effect of improving the dispersibility of the carbide particles through crushing, grinding, and mixing cannot be obtained, and if the process is performed for more than 24 hours, it is difficult to obtain the further effects of crushing, grinding, and mixing, resulting in a deterioration in production efficiency.
[0069] (Hot press conditions) In the HP process, a sintered body having a relative density of 95% or more is produced. The HP temperature for producing a sintered body having such characteristics is preferably 1400°C to 1800°C. If the HP temperature is too low, the relative density decreases and the strength of the composite material decreases, whereas if the HP temperature is too high, the crystal growth of molybdenum proceeds and the strength of the alloy decreases.
[0070] (Comparison with existing technology) In the prior art, a powder mixing method using mechanical alloying has been shown as a manufacturing method for a material in which a transition metal carbide is added to molybdenum (Patent No. 3271040 and JP 2000-129389 A, etc.). However, a high-energy mixing method in which carbide particles are embedded in molybdenum particles is not necessary to obtain the dispersibility of the carbide particles in the molybdenum composite material of the present invention. Note that mechanical alloying is not suitable as a manufacturing method for the molybdenum composite material of the present invention because it requires effort and cost, and the amount of powder that can be processed per batch is small, which leads to an increase in production costs and a decrease in production efficiency.
[0071] Conventionally, a sintering method has been used to densify the material by hot isostatic pressing (HIP) (Patent No. 3271040), but HIP is more expensive than HP and is therefore a technique that should be avoided when producing heat-resistant products that are consumables, such as evaporation boats. In the present invention, HP is used to obtain sintered bodies with a relative density of 98% or more, so HIP is not suitable and HP is appropriate.
[0072] Furthermore, in the past, spark plasma sintering (SPS) has been used as a sintering method (JP Patent Publication 2000-129389), but SPS is a method for producing relatively small samples and is not suitable for producing products for heat-resistant applications such as evaporation boats. HP is suitable as a manufacturing method for the molybdenum composite material of the present invention.
[0073] The technology disclosed in Patent No. 5546880 shows a material in which carbides of Ti, Zr, Hf, etc. are added to molybdenum and a manufacturing method thereof. The patent states that poor dispersion of carbide particles leads to insufficient strength, but does not specify the powder mixing method or dispersibility index, and does not present any information on how to obtain good dispersion of carbide particles in the molybdenum composite material of the present invention. Furthermore, the patent uses HIP as the sintering method, but HIP is more expensive than HP and should be avoided when producing heat-resistant products that are consumables such as evaporation boats. The patent states that "the relative density of sintered bodies obtained by general powder sintering methods is about 90%," and it is thought that HIP was used to obtain high-density sintered bodies, but in the present invention, sintered bodies with a relative density of 98% or more can be obtained by HP, so HIP is not suitable and HP is suitable.
[0074] The technology disclosed in Japanese Patent No. 5238259 shows a material in which titanium carbide, hafnium carbide, zirconium carbide, and tantalum carbide are added to molybdenum. The patent states that the powder mixing method is as follows: "Mo powder, carbide powder such as TiC, etc. are prepared as raw material powders, and mixed in a ball mill or the like. Mo powder with an average particle size of 5 μm or less and carbide powder with an average particle size of 2 μm or less are preferable, more preferably (average particle size of Mo powder > average particle size of carbide powder), and even more preferably [average particle size of Mo powder > 3 (average particle size of carbide powder)]. If the average particle size of the carbide powder is smaller than the average particle size of Mo powder, the carbide is more likely to be uniformly dispersed in the grain boundary phase of Mo." However, no indicator of dispersibility is specified, and information on obtaining the molybdenum composite material of the present invention is not sufficiently disclosed. Furthermore, the patent specifies that the aspect ratio of the carbide particles should be at least 2 and less than 20, and states that sintering at 1900°C or higher, or rolling or forging is suitable for obtaining such an aspect ratio. However, in the production of the molybdenum composite material of the present invention, sintering at 1900°C or higher is excessive and is unsuitable because it promotes grain growth of molybdenum. Furthermore, rolling and forging may cause anisotropy in strength and therefore may not be suitable for heat-resistant products such as deposition boards.
[0075] The present invention will now be further described with reference to specific examples.
[0076] Tables 1 and 2 show examples that are within the scope of the claims of this patent, as well as comparative examples to demonstrate the effectiveness of this patent.
[0077] In Examples 1 to 16, molybdenum powder and carbide powder were weighed out so as to have an additive concentration within the range claimed in the present patent, and then the mixed powder was crushed, pulverized, and mixed in a rod mill for 1 to 24 hours. The mixed powder was then hot pressed at 1750°C to obtain a sintered body. Test pieces were cut from the sintered body and various measurements were performed. The results showed that the dispersibility was within the range claimed in the present patent.
[0078] In Comparative Examples 1 to 10, molybdenum powder and carbide powder were weighed out so as to give addition concentrations outside the range of the present invention, and then the mixed powders were crushed, pulverized, and mixed in a rod mill for 1 to 24 hours. The mixed powders were then hot pressed at 1750°C to obtain sintered bodies, from which test pieces were cut out and various measurements were performed.
[0079] In Comparative Examples 11 to 16, molybdenum powder and carbide powder were weighed out to have addition concentrations within the range of the present invention, and then mixed in a tumbler mixer for 1 to 24 hours or in a rod mill for less than 1 hour. The mixed powder was then hot pressed at 1750°C to obtain a sintered body. Test pieces were then cut out from these sintered bodies and various measurements were performed.
[0080] Comparative Examples 17 and 18 show the results of various measurements of a commercially available pure molybdenum plate material and a molybdenum plate material containing lanthanum oxide, respectively. From the results in Tables 1 and 2, the inventors concluded that a sintered body containing molybdenum as the main component and at least one carbide selected from Ti carbide, Zr carbide, and Hf carbide in the range of 2 to 10 mass %, and having an average Voronoi division area of 80 μm 2The inventors have come to the understanding that a molybdenum composite material having a standard deviation / average value, which is the coefficient of variation of the Voronoi division area, of 1.8 or less will have superior strength and hardness after heating and smaller change in hardness than conventionally available pure molybdenum sheet materials and molybdenum sheet materials containing lanthanum oxide, and will satisfy the post-heat strength and hardness required for heat-resistant applications such as evaporation boats.
[0081] [Table 1]
[0082] [Table 2]
Claims
1. A molybdenum composite material which is a sintered body of a mixed powder of molybdenum powder and a carbide powder, the molybdenum composite material containing molybdenum as a main component and 2 to 10 mass % of at least one carbide selected from a carbide of Ti, a carbide of Zr, and a carbide of Hf, The average area of the Voronoi division with the carbide powder as the generating point is 80 μm 2 and the standard deviation / average value, which is the coefficient of variation of the area of the Voronoi division, is 1.8 or less. Molybdenum composites.
2. 2. The molybdenum composite material according to claim 1, wherein the maximum bending strength at room temperature after heating in a vacuum at 1800° C. for 8 hours is 1000 MPa or more, and the deformation behavior is ductile, the deformation behavior being determined by a push-bending method defined in JIS Z 2248 for a test piece cut into the shape of a No. 3 test piece defined in JIS Z 2248, and the test piece being bent without breaking when pushed 20 mm with a support distance of 20 mm, the test piece being considered to be ductile.
3. 2. The molybdenum composite material of claim 1, having a Vickers hardness of 200 HV or more after heating in a vacuum at 1800° C. for 8 hours.
4. 4. The molybdenum composite material according to claim 3, wherein the Vickers hardness reduction rate (%) before and after heating in a vacuum at 1800°C for 8 hours, calculated by subtracting the reduction in hardness after heating from the reduction in hardness before heating and dividing the reduction in hardness by the hardness before heating, is 30% or less.
5. 2. The molybdenum composite material according to claim 1, which is obtained by crushing and pulverizing said molybdenum powder and said carbide powder, mixing the resulting powder, and hot pressing said mixed powder.
6. The molybdenum powder has an average particle size D Ave The carbide powder has an average particle size D AveThe molybdenum composite material according to claim 5, wherein the average particle diameter (D50) is 1.5 to 3.0 μm and the median diameter (D50) is 1.0 to 2.5 μm.
7. The average particle diameter D of the mixed powder Ave The molybdenum composite material according to claim 5, wherein the average particle diameter (D50) is 1.5 to 3.5 μm and the median diameter (D50) is 1.0 to 3.0 μm.
8. A molybdenum composite material molded product obtained by molding the molybdenum composite material according to any one of claims 1 to 7 into a predetermined shape.
9. A step of preparing a molybdenum powder and at least one carbide powder selected from a Ti carbide powder, a Zr carbide powder, and a Hf carbide powder in a predetermined ratio; a step of crushing and pulverizing the molybdenum powder and the carbide powder, and mixing the powder to obtain a mixed powder having an average particle size D of 1.5 to 3.5 μm and a median diameter D of 1.0 to 3.0 μm; The mixed powder is sintered to obtain a sintered body mainly containing molybdenum and containing at least one carbide selected from a Ti carbide, a Zr carbide, and a Hf carbide in a range of 2 to 10 mass %, and the average area of Voronoi division with the carbide powder as a base point is 80 μm 2 a step of obtaining a molybdenum composite material having a standard deviation / average value, which is a coefficient of variation of the area of Voronoi division, of 1.8 or less; and a method for producing a molybdenum composite material comprising:
10. The method for producing a molybdenum composite material according to claim 9, wherein the step of obtaining the sintered body is carried out by hot pressing (HP) at a temperature of 1400°C or higher and 1800°C or lower.
11. The molybdenum powder has an average particle size D Ave The carbide powder has an average particle size D AveThe method for producing a molybdenum composite material according to claim 9, wherein the average particle diameter is 1.5 to 3.0 μm and the median diameter D50 is 1.0 to 2.5 μm.
12. The method for producing a molybdenum composite material according to claim 9, wherein the step of crushing, pulverizing and mixing the molybdenum powder and the carbide powder is carried out by a rod mill.
13. A method for producing a molybdenum composite material molded product, comprising molding the molybdenum composite material according to any one of claims 1 to 7 or a molybdenum composite material produced by the method for producing a molybdenum composite material according to any one of claims 9 to 12 into a predetermined shape to obtain a molybdenum composite material molded product.
Citation Information
Patent Citations
Method for preparing high-strength and high-plasticity molybdenum alloy
CN115007871A
Alarm sound producing device
JP1977038259A
Driving circuit for inverter
JP1980046880A
Molybdenum sintered compact and its manufacture
JP2000129389A
Molybdenum alloy and its manufacturing method
JP3271040B2
Cited By
Molybdenum composite material processed product for vacuum and high-temperature equipment and method for manufacturing molybdenum composite material processed product for vacuum and high-temperature equipment
JP2026148048A
Molybdenum composite material processed product for vacuum and high-temperature device and method for manufacturing molybdenum composite material processed product for vacuum and high-temperature device
JP7706033B1
